Stereological Changes in Rat Ventral Prostate Induced by Melatonin - Wannee Srivilai (2018)
Effects of melatonin on the ventral prostate of castrated rats supplemented with testosterone were studied using light microscopy. Stereological measurements were made of volume fractions of acini and stroma and surface fractions of glandular epithelium. From these figures and the weights of the glands, the volumes and surface areas were calculated, as well as the mean epithelial heights, mean acinar diameters, and mean distances between glandular acini. Doses of melatonin were varied, to verify its physiological and pharmacological effects. Castration without hormonal treatments produced atrophic changes, with decreases in acinar and stromal volume and widenings in the mean distances between the acini. None of these measurements differed among intact controls, sham‐operated controls, and testosterone‐supplemented castrated rats. In the castrated rats receiving both testosterone and melatonin, however, there were changes according to the doses of melatonin given. The animals receiving low doses of melatonin (50 and 400 μg daily) showed significant decreases in the volumes of the stroma and epithelium and the height of the epithelium. These stereological changes occurred without a significant reduction in the prostatic weights. The animals receiving the higher dose (800 μg daily) of melatonin showed no difference in any measurement compared with those of the testosterone‐supplemented castrated rats. In rats receiving 2,000 μg of melatonin daily, there were significant reductions in the weights of the prostates and the volumes of the acini. These results suggest a direct action of melatonin on the ventral prostate, and the effects depend on the dose given. Copyright © 1989, Wiley Blackwell. All rights reserved